2016
DOI: 10.1097/txd.0000000000000630
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel and Noninvasive Biomarkers of Acute Cellular Rejection After Liver Transplantation by Protein Microarray

Abstract: BackgroundAcute cellular rejection (ACR) is one of the main factors in transplanted organ failure in liver transplantation. A precise marker for diagnosing or predicting rejection is not currently available; therefore, invasive liver biopsy is standard procedure. To develop a noninvasive method for precise diagnosis of ACR, we evaluated autoantibodies from patient sera as potential biomarkers using protein microarrays (seromics).MethodsSera from hepatitis C virus–positive ACR patients were compared to three he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Many studies have evaluated the role of noninvasive biomarkers of TCMR among serum parameters of inflammation or mediators of T‐cell activation . Unfortunately, none of these biomarkers has been implemented hitherto because of their complexity, lack of reproducibility/validation, inaccuracy, or costs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have evaluated the role of noninvasive biomarkers of TCMR among serum parameters of inflammation or mediators of T‐cell activation . Unfortunately, none of these biomarkers has been implemented hitherto because of their complexity, lack of reproducibility/validation, inaccuracy, or costs .…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have identified some clinical predictors of TCMR, such as younger age, low MELD score, underlying autoimmune liver disease, elevated blood eosinophils count, and vitamin D deficiency, they are not sufficiently validated to guide clinical decisions. Biomarkers and immune function assays have been proposed, but again results are contradictory and they are not widely available …”
Section: Introductionmentioning
confidence: 99%
“…Many major rejection and injury features initially described in kidney transplants 31,44,45 are shared with heart 33,46‐48 and lung transplants, 35,49 indicating that rejection changes are not organ specific and are likely shared by liver transplants. Existing studies have established the potential utility of molecular assessment of liver biopsies 1,24‐25,50‐56 …”
Section: Introductionmentioning
confidence: 99%
“…The study by Massoud et al (24) identified the following seven markers: serum amyloid A protein (SAA), complement 4 (C4), fibrinogen, complement 1q (C1q), complement 3, heat shock protein 60, and heat shock protein 70. The study by Okubo et al (20) identified autoantibodies in sera by fold change and intensity to charge one of the following markers: multivesicular body protein 2B, potassium channel tetramerization domain containing 14, voltage-gated subfamily A regulatory beta subunit 3, and triosephosphate isomerase 1.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of Okubo et al (20) (20 AR cases, 80 samples) and Massoud et al (24) (33 AR cases, 62 samples) were similarly designed. The authors used proteomics and ELISA to test blood samples to discover possible markers of AR.…”
Section: Resultsmentioning
confidence: 99%